PILIHAN BAHASA MASYARAKAT SAMIN DALAM RANAH KELUARGA - Hari Bakti Mardikantoro (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2012)
The language choice of Samin society in Blora is an interesting phenomenon to study by the perspective of sociolinguistic since it is related not only to language aspect, but also to socio-cultural aspect. This study aims to reveal the firm of family language choice of Samin society in Blora and the socio-cultural factors that determine it. This research is a sociolinguistic study which is based on the language and culture phenomenon in relation to society In communicating among their family, Samin society use ngoko (low language level) Javanese, madya/krama (middle high language level) Javanese, do switch code, and mixed code, either from the ngoko Javanese to madya/karma Javanese or the vice versa.